ESTIMATING THE SAMPLING FREQUENCY AND ACCURACY OF SEDIMENT FLUX IN A LARGE ASIAN RIVER: THE RED RIVER SYSTEM (CHINA/VIETNAM) - Thi Ha, Dang; Coynel, Alexandar (Vietnam Journal of Science and Technology, 2015)
Based on dataset of daily water discharges and sediment concentrations of the Red River during 2005-2011 period, we have analyzed the influence of sampling frequency on uncertainty of sediment flux estimates and pointed out the need of adapted sampling frequency strategies. Seven kinds of sampling frequency from monthly to one sample every two days were tested for the Red River at LaoCai, PhuTho and SonTay stations and the Da and Lo Rivers. The results obtained showed that the range minimum-maximum flux estimates decrease significantly with increasing sampling frequencies and error values of simulation tended to approach 0%. If a deviation of simulated flux estimates lower than  ±15% from the reference fluxes is accepted, the Red River at LaoCai and PhuTho sites must be sampled at least 8 samples per month (i.e. twice-weekly) and the Red River at SonTay, the Da and Lo Rivers must be sampled at least 4 samples per month (i.e. weekly).